Lipopolysaccharide-specific bacteriophage for Klebsiella pneumoniae C3. - Tomás, J M (1985)
Bacteriophage FC3-1 is one of several specific bacteriophages of Klebsiella pneumoniae C3 isolated in our laboratory. Unlike receptors for other Klebsiella phages, the bacteriophage FC3-1 receptor was shown to be lipopolysaccharide, specifically the polysaccharide fraction (O-antigen and core region). We concluded that capsular polysaccharide, outer membrane proteins, and lipid A were not involved in phage binding. Mutants resistant to this phage were isolated and were found to be devoid of lipopolysaccharide O-antigen by several criteria but to contain capsular material serologically identical to that of the wild type. The polysaccharide fraction was concluded to be the primary phage receptor, indicating that it is available to the phage.